Recent Progress on Ligand-Protected Metal Nanoclusters in Photocatalysis - Meegle S. Mathew; Greeshma Krishnan; Amita Aanne Mathews; Kevin Sunil; Leo Mathew; Rodolphe Antoine; Sabu Thomas (Nanomaterials, 2023)
The reckless use of non-replenishable fuels by the growing population for energy and the resultant incessant emissions of hazardous gases and waste products into the atmosphere have insisted that scientists fabricate materials capable of managing these global threats at once. In recent studies, photocatalysis has been employed to focus on utilizing renewable solar energy to initiate chemical processes with the aid of semiconductors and highly selective catalysts. A wide range of nanoparticles has showcased promising photocatalytic properties. Metal nanoclusters (MNCs) with sizes below 2 nm, stabilized by ligands, show discrete energy levels and exhibit unique optoelectronic properties, which are vital to photocatalysis. In this review, we intend to compile information on the synthesis, true nature, and stability of the MNCs decorated with ligands and the varying photocatalytic efficiency of metal NCs concerning changes in the aforementioned domains. The review discusses the photocatalytic activity of atomically precise ligand-protected MNCs and their hybrids in the domain of energy conversion processes such as the photodegradation of dyes, the oxygen evolution reaction (ORR), the hydrogen evolution reaction (HER), and the CO2 reduction reaction (CO2RR).